Measurements of distalization and lateralization do not correlate with patient reported outcome measures following reverse shoulder arthroplasty - Sofia Griff; Noah E DiNapoli; James A Rhead; Garrett S Bullock; Brian R Waterman; Nicholas A Trasolini; Benjamin R Graves; Alan W Reynolds (Clinics in Shoulder and Elbow, 2026)
Background: The optimization of implant positioning in reverse shoulder arthroplasty produces evolving and conflicting data. The distalization-lateralization index (DLI) has been introduced as a measurement that combines both lateralization and distalization. This study aimed to determine whether legacy and novel measurements correlate with patient reported outcomes.Methods: Patients who underwent primary reverse shoulder arthroplasty at a single institution between 2016 and 2022 and had a minimum of 2 years of follow up were screened by retrospective chart review. Radiographs were used to measure the lateralization shoulder angle, distalization shoulder angle, acromiohumeral interval (AHI), acromiohumeral offset (AHO), and glenohumeral offset (GHO). DLI and ΔDLI were calculated from the ΔAHI and ΔAHO. A linear regression analysis was performed to identify correlations between any measurements and the postoperative American Shoulder and Elbow Surgeons (ASES) score.Results: Data were analyzed from 140 patients with an average age of 71 years and average follow up of 3.3 years. AHO had an adjusted mean difference of –0.29 (P=0.009) between high and low ASES score groups. There was a weak, but statistically significant association between the ASES score and the DLI (r=0.181, P=0.032) in the simple linear regression, but no association was found in the multivariable linear regression, β=0.46 (95% CI, –0.04 to 0.95; P=0.072).Conclusions: Increased DLI was found to be weakly associated with higher ASES scores in the univariate analysis, but not after controlling for other variables. Although the correlation was not statistically significant, both the DLI and GHO were associated with higher ASES scores in the multivariate analysis, warranting further study with larger patient cohorts.Level of evidence: III.